Regulated internalization of NMDA receptors drives PKD1-mediated suppression of the activity of residual cell-surface NMDA receptors. Issue 1 (December 2015) - Fang, Xiao-Qian; Qiao, Haifa; Groveman, Bradley; Feng, Shuang; Pflueger, Melissa; Xin, Wen-Kuan; Ali, Mohammad; Lin, Shuang-Xiu; Xu, Jindong; Duclot, Florian; Kabbaj, Mohamed; Wang, Wei; et al.
Abstract Background Constitutive and regulated internalization of cell surface proteins has been extensively investigated. The regulated internalization has been characterized as a principal mechanism for removing cell-surface receptors from the plasma membrane, and signaling to downstream targets of receptors. However, so far it is still not known whether the functional properties of remaining (non-internalized) receptor/channels may be regulated by internalization of the same class of receptor/channels. The N-methyl-D-aspartate receptor (NMDAR) is a principal subtype of glutamate-gated ion channel and plays key roles in neuronal plasticity and memory functions. NMDARs are well-known to undergo two types of regulated internalization – homologous and heterologous, which can be induced by high NMDA/glycine and DHPG, respectively. In the present work, we investigated effects of regulated NMDAR internalization on the activity of residual cell-surface NMDARs and neuronal functions. Results In electrophysiological experiments we discovered that the regulated internalization of NMDARs not only reduced the number of cell surface NMDARs but also caused an inhibition of the activity of remaining (non-internalized) surface NMDARs. In biochemical experiments we identified that this functional inhibition of remaining surface NMDARs was mediated by increased serine phosphorylation of surface NMDARs, resulting from the activation of protein kinase D1 (PKD1). Knockdown of PKD1 did not affect NMDAR internalization but prevented the phosphorylation and inhibition of remaining surface NMDARs and NMDAR-mediated synaptic functions. Conclusion These data demonstrate a novel concept that regulated internalization of cell surface NMDARs not only reduces the number of NMDARs on the cell surface but also causes an inhibition of the activity of remaining surface NMDARs through intracellular signaling pathway(s). Furthermore, modulating the activity of remaining surface receptors may be an effective approach for treating receptor internalization-induced changes in neuronal functions of the CNS.